Impacts of rainfall and soil conservation measures on soil, SOC, and TN losses on slopes in the black soil region, northeastern China - Haiyan Fang (Elsevier, 2021)
Water erosion significantly affects the productive black soils in Northeastern China. The aim of this study was to analyze the impacts of rainfall characteristics, slope, and soil conservation measures on soil, soil organic carbon (SOC), and total nitrogen (TN) losses and thus to help implement a rational soil loss control strategy. The present study was conducted using sampled soil, runoff, and soil loss data from the plots in the years 2014, 2015, and 2020 when the rainfall characteristics varied greatly. Studies found that soil, SOC, and TN losses on the 18 plots differed greatly, depending on soil conservation measures, slope and rainfall characteristics. Bare and up-downslope (UD) cultivated plots suffered the highest loss rates of soil, SOC, and TN. In 2014, annual loss rates of soil, SOC, and TN on the UD plots reached 5849, 88.55, and 6.84 t km−2 yr−1, respectively. In 2015, soil loss rate (SLR) on the UD plots approached 434.88 t km−2 yr−1 with SOC and TN loss rates of 5.83 and 0.44 t km−2 yr−1. In 2020, the mean SLR on the UD plots was 637.96 t km−2 yr−1 which was lower than that (i.e., 1385.61 t km−2 yr−1) on the bare plots. Annual loss rates of soil, SOC, and TN presented an increasing trend with increasing slope degree. The soil, SOC and TN control efficiencies of contour tillage and hedgerow planting on the 3° and 5° plots were around 90%. The mean SLR on the 53-m terraced plots was two times the tolerable value (i.e., 200 t km−2 yr−1). The size of terrace on steep slopes should be reconsidered, and slope length should be reduced. Bare and UD slopes must be implemented with rational soil conservation measures to control soil, TN, and SOC losses in the black soil region of northeastern China.